Gender stereotypes about sport and physical activity in adolescents - Alonso García, Gema; Pérez Muñoz, Salvador; Rodríguez Cayetano, Alberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Women still have numerous barriers to access to sport (Pérez-Ugena, 2020). This is due, as indicated by Monforte and Úbeda-Colomer (2019) to the fact that gender stereotypes still exist in our society. The aim of the study was to analyze gender stereotypes in Physical Activity and Sport in 51 adolescents, using sociodemographic variables and the CEGAFD instrument (Granda et al., 2018). The results show that, in most of the examples, the male sex is taken as the referent, highlighting also, significant differences in the variable of Gender Stereotypes in Sport.